INTEGRATING PROFESSIONAL COMPETENCE INTO FOREIGN LANGUAGE LEARNING FOR SPECIALIZED DISCIPLINES - Ravupova Mahzuna Zafar qizi; Abdullayeva Zarina Dilshodbekovna (TADQIQOTLAR, 2026)
ANNOTATION This article focuses on novel techniques of delivering foreign language lessons to the students of professional disciplines, which include medicine, engineering, and law, among others. In particular, the article stresses the necessity to apply professional vocabulary along with communication skills while delivering language lessons. It also suggests various methods of making language lessons more interesting and productive for the students, which may include task-based approach, role-playing, and project- based tasks, among others. This paper also describes certain difficulties that can be encountered while providing foreign language lessons to students whose major is different from languages, which includes varying levels of interest to this course and the level of language competence at the beginning of lessons, among other factors.